Edukasi Pemilahan Sampah Sebagai Upaya Preventif Mengatasi Masalah Sampah Di Lingkungan Sekolah - Anisza Ratnasari; Imaniar Sofia Asharhani; Marchelia Gupita Sari, Stefanus Rifaldo Hale, Hegar Pratiwi (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2019)
Small efforts can be done to protect the environment from rabbish heaps. Educating students about waste problems in the environment is needed to foster student awareness, so they are more concerned with the surrounding environment. Student participation is carried out with a culture of disposing rubbish. We know that there are many types of waste; there is organic waste that is easily decomposed, there is inorganic waste which is from processing synthetic product and there is hazardous and toxic materials. Students must be educated about these types of waste and how to treat them and also must be socialized to leave the old ways that just throw the garbage away, but also provide education to sort, select, and categorize waste as well as to develop a garbage bank so that it has economic value. If this is done, the practice of processing and utilizing waste becomes a concrete step in managing waste. Hopely, these tiny habits will be transmitted in the family and communities which allows to reduce environmental problems caused by garbage.